Outline of the U.S. legal system. (Bureau of International Information Programs, United States Department of State, 2004)
Every business day, courts throughout the United States render decisions that together affect many thousands of people. Some affect only the parties to a particular legal action, but others adjudicate rights, benefits, and legal principles that have an impact on all Americans. This book surveys that system. Much of the discussion explains how U.S. courts are organized and how they work. This introduction seeks to familiarize readers with the basic structure and vocabulary of American law, and afford a sense of how the U.S. legal system has evolved to meet the needs of a growing nation and its ever more complex economic and social realities.